A unilateral open-lip schizencephaly in a neonate: A rare case report - Seth Kwadjo Angmorterh, PhD; Kafui Kossi Kekessie, MB, ChB; Riaan van de Venter, PhD; Mariella Mawunyo Amoussou-Gohoungo, BSc; Adam Inusah, BSc; Huseini Alidu, PhD; Portia Mamle Angmorterh, MPhil; Cosmos Yarfi, MPhil; Sonia Aboagye, MSc; Christian Kwaku Agbewoavi, BSc; Daniel Opoku-Gyamfi, BSc; Rhoda Gbodzi, BSc; et al. (Radiology Case Reports)
Schizencephaly is a rare congenital central nervous system (CNS) developmental disorder characterized by abnormal cleft extending from the lateral ventricles to the cerebral cortex. Globally, very few cases have been reported in the literature and none from Ghana to the best of our knowledge. Herein, we report a case of schizencephaly in a Ghanaian neonate who presented with suspected ventriculomegaly during a routine antenatal screening. A postnatal ultrasound (US) and computed tomography (CT) scans of the brain revealed a large cerebrospinal fluid (CSF) filled cleft extending from the right lateral ventricle to the right frontotemporal cortex. There was no shift of the midline of the brain and posterior fossa appeared normal. A referral to a pediatric neurologist was made for early intervention, after a diagnosis of unilateral open-lip schizencephaly was made. Antenatal visits are crucial in picking up schizencephaly. Although schizencephaly is a rare congenital disorder, it does occur in Ghana, and it has significant effects on development and function. This condition can also present as ventriculomegaly, focal cortical dysplasia, grey matter heterotopias and porencephaly and therefore thorough radiological investigations are imperative to make a timeous and accurate diagnosis. A trans-fontanelle US and noncontrast head CT scan can be very useful in diagnosing schizencephaly. Treatment and management of schizencephaly are linked to the signs and symptoms and neurorehabilitation plays a pivotal role currently to enhance patients’ quality of life.